Gender, migration and domestic work: Space and time in the discourse of albanian domestic workers in Athens - Kambouri, Helen (The Greek Review of Social Research, 2007)
<div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 365.165px; transform: rotate(0deg) scale(1.16753, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.9824">This article explores the relationship between gender and migration from the <div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 382.978px; transform: rotate(0deg) scale(1.06394, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.51080000000013">perspective of everyday life. It is based on a series of focus group discussions with <div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 400.791px; transform: rotate(0deg) scale(1.0266, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.32720000000006">Albanian women who work in the domestic sector. The analysis explores the gendered <div style="font-size: 12.2681px; font-family: serif; left: 101.621px; top: 418.603px; transform: rotate(0deg) scale(1.00795, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.3464">ways in which these women describe, discuss and evaluate their personal experiences of <div style="font-size: 12.2681px; font-family: serif; left: 101.621px; top: 436.416px; transform: rotate(0deg) scale(1.02502, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.3596">space and time. Although there is a great diversity in these experiences, their discourse <div style="font-size: 12.2681px; font-family: serif; left: 101.621px; top: 454.23px; transform: rotate(0deg) scale(1.0425, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.29600000000005">is dominated by the fact that their everyday life has been overtaken by the space and <div style="font-size: 12.2681px; font-family: serif; left: 101.62px; top: 472.043px; transform: rotate(0deg) scale(1.02322, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.3968000000001">time of domestic work. The paper argues that the impact of this overtaking is twofold: <div style="font-size: 12.2681px; font-family: serif; left: 101.62px; top: 489.856px; transform: rotate(0deg) scale(1.06803, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.0091999999999">on the one hand, it accounts for the isolation that Albanian domestic workers often <div style="font-size: 12.2681px; font-family: serif; left: 101.62px; top: 507.669px; transform: rotate(0deg) scale(1.10084, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.08119999999997">experience as migrants in a foreign country, but also for their unequal position as <div style="font-size: 12.2681px; font-family: serif; left: 101.62px; top: 525.482px; transform: rotate(0deg) scale(1.09752, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.22639999999996">women within the Albanian family; on the other hand, however, it also leads to a <div style="font-size: 12.2681px; font-family: serif; left: 101.62px; top: 543.294px; transform: rotate(0deg) scale(1.06962, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.6392000000001">questioning of gender stereotypes that prevail in both the country of origin and the <div style="font-size: 12.2681px; font-family: serif; left: 101.619px; top: 561.107px; transform: rotate(0deg) scale(1.08965, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="424.1280000000001">host country, as the limits between paid and unpaid, private and public, male and <div style="font-size: 12.2681px; font-family: serif; left: 101.619px; top: 578.92px; transform: rotate(0deg) scale(1.03198, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_125_0" data-canvas-width="211.5563999999999">female space and time are being challenged.